2020
DOI: 10.1109/access.2020.3032760
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Based Study for Managing Hospital Resources by Reducing Patient Waiting Time

Abstract: Labs, Ultrasound and the ECG sections were included in the computer-based simulation model with the aim to find the bottleneck departments as they are the main cause of waiting time in the hospital. These bottlenecks are anticipated due to the lack of an optimized model, which has been addressed in this simulation. Based on the simulation study an optimized model is proposed to the hospital administration where the resources are readjusted resulting in the utilization of underutilized departments and decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…A simulation-based study of such essential ancillary services as X-rays, Labs, and Ultrasound concluded the need for an optimisation model to ensure the adjustment of resources in bottleneck areas like the ED and outpatients (Ahmad et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A simulation-based study of such essential ancillary services as X-rays, Labs, and Ultrasound concluded the need for an optimisation model to ensure the adjustment of resources in bottleneck areas like the ED and outpatients (Ahmad et al. , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of waiting people at the Inspection is rise before off-hours, which may indicate that patients are eager to complete the medical test before off hours to avoid dragging the test to the next day. Previous studies have shown that sampling examinations are required for the majority of patients, and the waiting time for sampling examinations is long 27 . In Table 3 , concurrence of multiple diseases does not result in a longer diagnostic time for physicians, but significantly increases the length of time used after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Not all doctors and nurses engaged in triage are trained in emergency medicine. Triage training is quite variable across the island [48,49].…”
Section: Improving Triage Systemsmentioning
confidence: 99%